Fibre optic interconnecting devices and passive components. Conditions for testing the protection against dust and water ingress of passive optical protective housings and hardened fibre optic connectors (IP5X, IPX4, IPX5, IPX6). (10th December 2021) - British Standards Institution,
No abstract available